2014
DOI: 10.1039/c4cc04123b
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of spin-crossover coordination polymers with large thermal hysteresis loops prepared by nanoparticle spin coating

Abstract: This communication describes the synthesis of spin-crossover nanoparticles, which can disperse in various organic solvents without an excess amount of surfactants. The nanoparticles form homogeneous thin films on substrates by spin coating. The films show abrupt spin transitions with large thermal hysteresis loops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
1
11
0
3
Order By: Relevance
“…The n -butyronitrile solution of complex 1 ·CH 3 OH exhibited color changes from pale pink to purple by adding of CF 3 SO 3 H (Figure , inset). In the UV-vis absorption spectra, the broad-band center at ∼550 nm can be assigned to a metal-to-ligand charge transfer (MLCT) band from the metal d π -orbitals into π*-orbitals of the ligands. , The addition of CF 3 SO 3 H, with the stoichiometric ratio of 1 ·CH 3 OH/CF 3 SO 3 H, from 1:0.1, 1:0.2, 1:0.3, ..., 1:1, resulted in the growth of the broad-band center at ∼550 nm, as well as generation of a new band center at 400 nm; the latter can be assigned to the d–d transition of the LS state Fe­(II) ions. , The foregoing spectral change suggested that the protonation of amino groups resulted in partial spin state conversion to give a mixture of HS and LS state species. It then can be presumed that the protonation of amino groups, on the one hand, leads to an increase in the π-accepting ability of ligand bipy-NH 2 (as have been confirmed by the growth of the MLCT band); on the other hand, it generates strong anion-ligand electrostatic interactions between CF 3 SO 3 –NH 2 and bipy–NH 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The n -butyronitrile solution of complex 1 ·CH 3 OH exhibited color changes from pale pink to purple by adding of CF 3 SO 3 H (Figure , inset). In the UV-vis absorption spectra, the broad-band center at ∼550 nm can be assigned to a metal-to-ligand charge transfer (MLCT) band from the metal d π -orbitals into π*-orbitals of the ligands. , The addition of CF 3 SO 3 H, with the stoichiometric ratio of 1 ·CH 3 OH/CF 3 SO 3 H, from 1:0.1, 1:0.2, 1:0.3, ..., 1:1, resulted in the growth of the broad-band center at ∼550 nm, as well as generation of a new band center at 400 nm; the latter can be assigned to the d–d transition of the LS state Fe­(II) ions. , The foregoing spectral change suggested that the protonation of amino groups resulted in partial spin state conversion to give a mixture of HS and LS state species. It then can be presumed that the protonation of amino groups, on the one hand, leads to an increase in the π-accepting ability of ligand bipy-NH 2 (as have been confirmed by the growth of the MLCT band); on the other hand, it generates strong anion-ligand electrostatic interactions between CF 3 SO 3 –NH 2 and bipy–NH 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Up to now, the synthesis of several dozens of SCO complexes as nanoparticles or nanorods has been reported in the literature with particle sizes ranging from a few nm to several hundreds of nm. In many cases the particles could be re‐dispersed in solvents and further processed to form films, surface patterns, and nanocomposite materials . Recently, more complex architectures, such as core–shell particles, multilayer films, hybrid plasmonic, and fluorescent SCO particles have been also synthesized attesting a certain degree of maturity of the field and providing scope for the development of multifunctional nanomaterials displaying synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…This provides molecular, 1D, 2D and 3D motives with practically any desired transition temperature, hysteresis, abruptness, and completeness of the SCO, whose spin state can be communicated by means of temperature change, pressure, light irradiation, magnetic field or guest inclusion . SCO complexes can be processed to different functional materials: nanoparticles, thin films, surface motives,, composites,, gels, etc.…”
Section: Introductionmentioning
confidence: 99%